Defects induced resistive switching behavior in Ca doped YMnO3–based non–volatile memory devices through electronic excitations. (January 2021) - Gadani, Keval; Rathod, K.N.; Dhruv, Davit; Shrimali, V.G.; Rajyaguru, Bhargav; Joseph, Joyce; Joshi, A.D.; Pandya, D.D.; Asokan, K.; Solanki, P.S.; Shah, N.A.
Abstract: Defect induced structural, microstructural, resistive switching (RS) characteristics and related responsible charge conduction mechanisms of Y0·95 Ca0·05 MnO3 (YCMO) manganite films, grown on single crystalline ( 100 ) Nb:SrTiO3 (SNTO) substrates (0.2 wt% Nb doped at Ti–site in SrTiO3 ), are reported in this communication. Films were irradiated by 100 MeV O +7 swift heavy ions (SHI) with different ion fluence. Structural studies were performed using X–ray diffraction (XRD) and XRD φ–scan measurements for all pristine and irradiated films. Atomic force microscopy (AFM) measurement was performed to understand the granular morphology and surface modifications in YCMO films due to SHI irradiation. Observed RS behavior has been ascribed to the trapping–detrapping processes, modifications in the depletion region, movement of oxygen vacancies and tunneling process across the interface barriers between YCMO and SNTO. Various models and mechanisms have been employed to understand the observed charge transport across the interfaces. All the films show endurance and retention behaviors that suggest the reproducibility, dynamic stability and reliability of presently studied films as non–volatile memory devices. Highlights: PLD grown Y0·95 Ca0·05 MnO3 manganite films on Nb:SrTiO3 substrates. 100 MeV O +7 ions irradiation performed with different fluences i.e. 1 × 10 11 to 1 × 10 13 ions/cm 2 . Resistive Switching effect of YCMO thin film has been studied at room temperature. Defects induced modification of structural and microstructural properties were investigated. Role of oxygen vacancies and local annealing effect in RS effect were discussed.